Programme de Francais. Classes Secondaires de Langue Francaise (French Program. Secondary Classes in French Language) - Ontario Dept. of Education, Toronto; Ontario Dept. of Education, Toronto ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1964)
GRADES OR AGES: Grades 9-13. SUBJECT MATTER: French (for French-speaking students). ORGANIZATION AND PHYSICAL APPEARANCE: The guide is in French. It is divided into five sections--spoken language, grammar, spelling, composition, and "explication de texte." Within each section a curriculum is outlined for 2-, 3-, 4-year programs at each grade level. The guide is offset printed and staple-bound with a paper cover. OBJECTIVES AND ACTIVITIES: No objectives are mentioned. General suggestions for activities focus on content rather than procedures. INSTRUCTIONAL MATERIALS: A short bibliography follows the list of activities for each level. STUDENT ASSESSMENT: No provisions. (RT)
ERIC Note: Curriculum RP-46 (Rev. 1964).
Educational level discussed: Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Curriculum Guides; French; Secondary Education